Highly selective SPEEK/ENR blended polymer electrolyte membranes for direct methanol fuel cell. (September 2020) - Wan Mohd Noral Azman, W.N.E.; Jaafar, J.; Salleh, W.N.W.; Ismail, A.F.; Othman, M.H.D.; Rahman, M.A.; Rasdi, F.R.M.
Abstract: Sulfonated poly (ether ether ketone) (SPEEK) at higher degrees of sulfonation (DS) produced high proton conductivity, but it is impractical for DMFC application due to excessive swelling and severe methanol crossover. In this study, a novel blended membrane based on SPEEK at higher degrees of sulfonation (DS) of 80% and epoxidized natural rubber (ENR-50) are prepared at different mass ratio of SPEEK to ENR-50 (9.5:0.5, 9.0:1.0, 8.5:1.5, 8.0:2.0, and 7.5:2.5) via solution intercalation method. The influence of ENR-50 loading on the physical properties of SPEEK blends membranes was investigated and compared with the pristine SPEEK and Nafion117 membranes. The blended membranes were characterized by FTIR, which showed a successful chemical interaction between ENR-50 and SPEEK matrix. SEM images revealed a uniform dispersion of ENR-50 droplets in the polymer structure. The water uptake and methanol permeability of SPE50 membrane were found to be decreased with increasing of ENR-50 content. The highest proton conductivity of SPE50 membrane obtained was 47% higher than pure SPEEK, whereas the lowest permeability value obtained was 21 times lower than Nafion117 membrane. Consequently, incorporation of ENR-50 into SPEEK matrix has substantially enhanced the selectivity of the membrane by five folds. Apparently, this newly developed SPE blend membrane can be listed as one of the potential proton electrolyte membranes for the usage in DMFCs. Graphical abstract: Image 1 Highlights: A novel proton electrolyte membrane was developed for DMFC applications. SPEEK at a high degree of sulfonation was incorporated with ENR-50, a green based material, at various ratios. This novel membrane displayed encouraging advantages over Nafion117 on the methanol permeability and selectivity.